Analyzing the effects of system quality on the net benefits of the village financial system (Siskeudes): information quality and user satisfaction as mediating variables / Amir Mahmud ... [et al.] - Mahmud, Amir; Prayogo, Dedy; Sosilawati, Nurdian; Handayani, Bestari Dwi; Mardi, Mardi (UiTM Press, 2023)
All villages in Indonesia use the village financial system, namely Siskeudes. The village government uses Siskeudes to create a financial statement to achieve transparency and accountability. The research attempted to analyze information quality and user satisfaction as mediators of the Siskeudes system quality towards net benefits. In particular, the study examined the reciprocal relation between the Siskeudes system quality, information quality, user satisfaction, and net benefits based on the updated Delone & McLean Information System Success Model. The sample consisted of 68 Village Governments of the Semarang Regency. We used survey questionnaires to collect the data and partial least squares structural equation modeling (PLS-SEM) to analyze them. The study indicated that information quality is supported in mediating system quality towards user satisfaction and net benefits. The research also proved that user satisfaction mediated system quality and information quality towards net benefits. Then, siskeudes information quality and user satisfaction did not mediate the system quality to net benefits. The direct effect of variables supported each success dimension of the model. Siskeudes is the best system and information to create good village governance. It is helpful to build the stakeholders' decisions and public trust. This research provides valuable theoretical and practical implications for the government and researchers.